Congruence between Teachers' Spoken Discourse and Students' Vocabulary Levels: Is the Gap Too Wide?. Issue 1 (2nd January 2022) - Creighton, Graham
Abstract: In international schools where English is the language of learning and teaching there are many students whose first language is not English and whose low vocabulary levels inhibit their chances of taking full advantage of their education. Not only must students comprehend the high-frequency vocabulary that make up general English usage, they also need the mid-frequency and academic vocabulary used by their teachers. In this article I report on the vocabulary levels of grade 9 and 10 English as a Second Language (ESL) students at an international high school and the vocabulary profile of their teachers' spoken discourse. Results indicated a gap between the vocabulary level of the ESL students and the vocabulary used by the teachers. A better understanding of this gap would put English teachers in a stronger position to assist students to reach the vocabulary levels necessary for them to make sense of their lessons.